KEPASTIAN HUKUM SERTIFIKASI HALAL PADA OBAT-OBATAN DIKAITKAN DENGAN JAMINAN PRODUK HALAL - Deni Hudaefi; Martin Roestamy; Achmad Jaka Santos Adiwijaya (Magister Hukum Sekolah Pascasarjana Unida, 2021)
Indonesia is a country with the largest Muslim population in the world. In Islam, it is forbidden to consume any haram food. The state is currently obliged to provide protection and guarantee the halalness of products consumed by the public.The purpose of this study is to analyze the urgency of implementing Halal Drug Certification and to find out the Legal Certainty of Halal Certification related to Halal Product Guarantee.The approach method used in this research is normative juridical, where the law is conceptualized as a norm, rule, principle or dogma. The data collection techniques in this research are through the literature study, interviews and the using of qualitative analysis.Based on the results of the research, the halal certification implementation of drugs in Indonesia is urgently needed. The 90% of raw materials of it are imported from non-Muslim countries, so the drugs that circulate in Indonesia must be certified halal supported by the Halal Inspection Agency. However, the administrative penalty applied towards the violators of Halal Product Guarantee need to be switched to the criminal law or the public law analized from the point of view of the community concern.